Aspects of the morphology, life cycle and epidemiology of Toxocara species and Toxascaris Leonina - Tekele, Girma Mekete (University of the Free State, 2003)
The present study has provided detailed and comprehensive information on the morphological aspects, life cycle, and epidemiology of Toxocara canis, Toxocara cati and Toxascaris leonina. The overall results of the study results are briefly summarized as follows: 1. In the morphological studies of these parasites, it has been observed that there are gross morphological similarities in the developmental stages of T. canis, T. cati and T. leonina. However, closer and detailed observations have revealed that the various developmental stages differ from one another in their fine morphological features. The observed morphological differences were: a. Eggs of T. canis and T. cati look very similar under the light microscope, in some eggs it seems that the surface pits and ridges of T. canis are larger and coarser than in the eggs of T. cati. However, unlike the eggs of Toxocara spp., eggs of T. leonina have no surface pits and ridges but are smoother on the surface. b. Second-stage larvae of T. canis recovered from the eggs and from the infected tissues of mice were stumpy and vigorously motile. The larval stages from both sources were similar in their morphological features and had comparable size measurements indicating that larval stages did not undergo development in the paratenic host. Like the larvae of T. canis, second-stage larva of T. cati recovered from the eggs and from the infected tissues of mice were stumpy and vigorously motile. The larval stages from both sources were similar in their morphological features and had comparable size measurements. The second-stage larvae of T. canis recovered from eggs or from tissues of mice had a greater width than the comparable second-stage larvae of T. cati. Unlike the larval stages recovered from the embryonated eggs of T. leonina, larvae recovered from infected tissues of mice were longer and wider and had more distinct morphological features. This indicated that larval stages recovered from the tissues of infected mice had probably undergone development to third-stage larvae. c. Adults T. canis, T. cati and T. leonina resemble each other in their gross morphological features, but also differ in their detailed and fine structural features. The major differences were on the shape of cervical alae, the presence or absence of an esophageal ventriculus, the position of the vulva in the female worms, as well as the number and arrangement of papillae on the tail of the male worms. d. Precloacal median papilla were recorded and described in males of T. canis and T. cati. Previous researchers did not describe the presence of these structures in male Toxocara spp. worms. In the present study, a female T. canis worm with a length of 27.5 cm was recovered from an infected dog and it was larger than any recorded in the literature. 2. In the study of the modes of transmission of ascarids, it has been observed that transplacental transmission of T. canis occurred in mice infected during but not before pregnancy. Transmammary transmission of T. canis and T. cati larvae had also occurred in mice infected prior to or during pregnancy. However, unlike in T. canis and T. cati, had neither transplacental nor transmammary transmission occurred in T. leonina. Larval stages were recovered from most tissues and organs of infected mice, and the larvae gradually accumulated in various extraintestinal tissues for the three ascarid species and especially in the brain of mice infected with T. canis. 3. The study on T. leonina transmission to the definitive hosts through experimentally infected mice as paratenic host, has indicated that dogs can be infected by ingesting infected tissues of mice that were infected with T. leonina infective eggs originally obtained from dogs. However, in cats this was not possible and it has been suggested that cats may not be the proper definitive host for T. leonina originating from dogs. 4. In an epidemiological survey of Toxocara spp. T. leonina, and other intestinal helminths of dogs and cats in Jimma, Southwestern Ethiopia, it was shown that the overall prevalence rates for parasitic infection were 60.78% in faecal samples of dogs from the environment, 78.60% in faecal samples of dogs taken from the rectum, 66.23% in faecal samples of cats and 33.38% in soil samples were recorded. Parasite species identified were Toxocara canis, T. cati, Toxascaris leonina, hookworms, Spirocerca lupi, Trichuris vulpis, taeniids, Ascaris species and Strongyloides species. A relatively high mean egg count of 15.25 was observed for T. canis in dog faecal droppings collected from the environment. The potential of these parasites as a cause of zoonotic infections, ways of prevention of infection and control measures were discussed.

Die huidige studie verskaf omvattende inligting met betrekking tot aspekte van die morfologie, lewensiklus, en epidemiologie van Toxocara canis, Toxocara cati en Toxascaris leonina. Die resultate van die studie word kortliks as volg opgesom: 1. In die morfologiese studie van hierdie parasiete is waargeneem dat daar belangrike morfologiese ooreenkomste tussen die ontwikkelende stadiums van T. canis, T. cati en T. leonina bestaan. ‘n Deeglike en indiepte ondersoek het egter aangetoon dat die onderskeie stadiums op die fyner morfologiese vlak wel van mekaar verskil. Die waargenome verskille in morfologie was die volgende: a. Eiers van T. canis en T. cati lyk baie dieselfde onder die ligmikroskoop, in sommige eiers blyk dit asof die oppervlakgaatjies en -riwwe van T. canis groter en growwer is as in die eiers van T. cati. In die geval van T. leonina besit die eiers egter geen sodanige oppervlakgaatjies en -riwwe nie en is die oppervlak in hierdie spesie gladder. b. Tweede larwaal stadiums van T. canis wat uit eiers asook van geïnfekteerde muisweefsel verkry is, was kort, dik en baie beweeglik. Die larwes van beide bronne het ten opsigte van hul morfologiese eienskappe ooreengekom en het ook goed vergelyk in liggaamgroottes wat ‘n aanduiding is dat die larwes nie ontwikkeling in die parateniese gasheer ondergaan het nie. Net soos in die geval van T. canis, was die tweede larwaalstadium van T. cati herwin uit eiers sowel as geïnfekteerde muisweefsel, ook kort, dik en baie beweeeglik. Die larwaalstadiums vanuit beide bronne het morfologies sowel as in hul liggaamsgroottes ooreengekom. Die tweede larwaalstadiums van T. canis vanuit eiers of muisweefsel was wyer as die ooreenstemmende tweede larwaalstadium van T. cati. Anders as die larwaalstadiums verkry uit geëmbrioneerde eiers van T. leonina, was die larwes herwin uit geïnfekteerde muisweefsel langer en wyer met onderskeidende morfologiese kenmerke. Hierdie verskille dui moontlik daarop dat die larwes vanuit geïnfekteerde muisweefsel moontlik ontwikkeling na die derde larwaalstadium ondergaan het. c. Volwassenes van T. canis, T. cati en T. leonina toon baie ooreenkomste in hulle algemene morfologie, maar verskil ook op grond van hul fyner strukture. Die hoof verskille is in die vorm van die nekvleuels, die teenwoordigheid of afwesigheid van ‘n esofageale ventrikulus, die posisie van die vulva in die vroulike wurms, asook die getal en rangskikking van papillas op die stert van die manlike wurms. d. Prekloakale mediane papillas is waargeneem en beskryf in die mannetjies van T. canis en T. cati. Hierdie strukture is nooit voorheen deur navorsers in mannetjies van Toxocara spp. beskryf nie. In die huidige studie is ‘n wyfie T. canis van 27.5 cm in ‘n geïnfekteerde hond gevind, hierdie wurm was langer as enige waarnemings in die literatuur. 2. In die studie van die oordragingsmetodes by verteenwoordigers van die Ascariidae, is waargeneem dat transplasentale oordraging by T. canis in muise plaasgevind het wat tydens en nie voor swangerskap geïnfekteer is nie. Oordraging van larwes van T. canis and T. cati tydens die soogtyd het ook plaasgevind in muise wat voor of tydens swangerskap geïnfekteer is. Anders as in T. canis en T. cati het transplasentale oordraging en oordraging tydens die soogtyd glad nie in T. leonina voorgekom nie. Larwale stadiums is uit die meeste weefsel en organe van geïnfekteerde muise herwin, en die larwes van die drie spesies het geleidelik in die onderskeie ekstra-intestinale weefsel opgehoop, veral in die brein van die muise wat met T. canis geïnfekteer was. 3. Die studie van oordraging van T. leonina na die bepalende gasheer deur muise wat eksperimenteel geïnfekteer is, het aangedui dat honde wel geïnfekteer kan word deur muisweefsel in te neem wat besmet is met infektiewe T. leonina eiers wat oorspronklik van honde verkry is. In katte was dit egter nie moontlik nie en word voorgestel dat katte dalk nie die korrekte bepalende gasheer vir T. leonina is wat oorspronklik uit honde verkry is nie. 4. In ‘n epidemiologiese opname van Toxocara spp. T. leonina, en ander intestinale helminte van katte en honde in Jimma, suidwestelike Etiopië, is aangetoon dat die algemene persentasie besmetting vir parasitiese infeksies 60.78% in fekale hondemonsters uit die omgewing was, 78.60% in fekale hondemonsters vanuit die rektum, 66.23% in fekale katmonsters en 33.38% in grondmonsters. Parasietspesies wat geïdentifiseer is, was die volgende; Toxocara canis, T. cati, Toxascaris leonina, haakwurms, Spirocerca lupi, Trichuris vulpis, verteenwoordigers van die Taeniidae, Ascaris spesies en Strongyloides spesies. ‘n Relatiewe hoë gemiddelde eiertelling van 15.25 is vir T. canis in hondemis waargeneem wat uit die omgewing versamel is. Die potensiaal van hierdie parasiete as ‘n oorsaak van soönotiese infeksies, maniere om infeksies te voorkom en beheermaatreëls is bespreek.
Dissertation (M.Sc. (Zoology and Entomology))--University of the Free State, 2003
Keywords: Toxocara; Cats -- Parasites; Veterinary clinical pathology; Dogs -- Parasites; Nematodes